Thermodynamic analysis of a gamma type Stirling engine in an energy recovery system. (1st June 2018) - Sowale, Ayodeji; Kolios, Athanasios J.; Fidalgo, Beatriz; Somorin, Tosin; Parker, Alison; Williams, Leon; Collins, Matt; McAdam, Ewan; Tyrrel, Sean
Highlights: The performance of Stirling engine integrated to a micro-combustor in the NMT system was investigated. Energy recovery and power generation of 27 Wh/h from combustion of human faeces. The integrated position of the Stirling engine to the micro-combustor is highly paramount. Sensitivity of the performance of the Stirling engine to working gas temperature. Requirements for optimum performance of the Stirling engine for integration with micro-combustor. Abstract: The demand for better hygiene has increased the need for developing more effective sanitation systems and facilities for the safe disposal of human urine and faeces. Non-Sewered Sanitary systems are considered to be one of the promising alternative solutions to the existing flush toilet system. An example of these systems is the Nano Membrane Toilet (NMT) system being developed at Cranfield University, which targets the safe disposal of human waste while generating power and recovering water. The NMT will generate energy from the conversion of human waste with the use of a micro-combustor; the heat produced will power a Stirling engine connected to a linear alternator to generate electricity. This study presents a numerical investigation of the thermodynamic analysis and operational characteristics of a quasi steady state model of the gamma type Stirling engine integrated into a combustor in the back end of the NMT system. The effects of the working gas, at different temperatures, on the Stirling engine performance are also presented. The results show that with the heater temperature of 390 °C from the heat supply via conduction at 820 W from the flue gas, the Stirling engine generates a daily power output of 27 Wh/h at a frequency of 23.85 Hz.